2022
DOI: 10.3389/fmed.2022.840910
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial Anaerobic Meningitis Detected by Next-Generation Sequencing: Case Report and Review of the Literature

Abstract: BackgroundAnaerobic meningitis is a severe central nervous system infection associated with significant neurological sequelae and high mortality. However, the precise detection of causative pathogen(s) remains difficult because anaerobic bacteria are difficult to culture. Next-generation sequencing is a technology that was developed recently and has been applied in many fields. To the best of our knowledge, the use of next-generation sequencing for cerebrospinal fluid analysis in the diagnosis of anaerobic men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Most of the cases and studies performed previously in our hospital identified only mono-bacterial anaerobe meningitis [ 36 , 37 ]. Moreover, only a few case reports of polymicrobial mixed aerobe–anaerobe meningitis have been published worldwide [ 1 , 33 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the cases and studies performed previously in our hospital identified only mono-bacterial anaerobe meningitis [ 36 , 37 ]. Moreover, only a few case reports of polymicrobial mixed aerobe–anaerobe meningitis have been published worldwide [ 1 , 33 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polymicrobial meningitis including anaerobes is very rare nowadays, but was reported in the past as a complication in ear–nose–throat (ENT), abdominal, or gynecological infections, or other rare clinical malformations, such as Currarino syndrome (characterized by the triad of sacral anomaly, anorectal malformation, and presacral mass) [ 1 , 2 ]. Of these, otolaryngological infections are a known predisposing factor mainly for anaerobic meningitis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers have shown that. [ 23 , 24 ] For infections of unknown origin, mNGS has expanded the bacterial detection spectrum and is a vital detection method. It is widely used in the early diagnosis and precise treatment of clinical infectious diseases.…”
Section: Discussionmentioning
confidence: 99%